(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Fault tolerance is a significant field of wireless sensor network research. Many sensor nodes are installed under aggressive and unpredictable environmental conditions, so environmental changes typically weaken the sensor nodes in many locations, leading to fragmented connections and the network division into several small networks. Sensor nodes in these partitioned networks are only capable of detecting the events that occur in their partition and are not able to disseminate data to the base station. Here, we suggested a method to identify partitions that may be compromised by natural disasters and reconfigure the partitioned network for the network’s proper functioning. In that we have used MMUs to set up a backbone infrastructure to restore connectivity between the partitioned networks at the required places, on the directions given by the base station.